2014
DOI: 10.5021/ad.2014.26.3.321
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Photodynamic Therapy with Topical Methyl Aminolevulinate versus 5-Aminolevulinic Acid for Facial Actinic Keratosis with Long-Term Follow-Up

Abstract: BackgroundFew studies have compared the efficacy, cosmetic outcomes, and adverse events between 5-aminolevulinic acid photodynamic therapy (ALA-PDT) and methyl aminolevulinate-PDT (MAL-PDT) for actinic keratoses (AKs) in Asian ethnic populations with dark-skin.ObjectiveWe retrospectively compared the long-term efficacy, recurrence rates, cosmetic outcomes, and safety of ALA-PDT versus MAL-PDT for facial AKs in Koreans.MethodsA total of 222 facial AKs in 58 patients were included in this study. A total of 153 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 41 publications
1
30
0
1
Order By: Relevance
“…However, only a few small clinical studies have directly compared ALA‐ with MAL‐PDT and this has only been done for AKs and nBCC. To our knowledge, no studies have compared the efficacy of ALA‐ and MAL‐PDT for sBCC and BD . Although in vitro studies have shown some differences concerning penetration and accumulation between the two compounds, which can be demonstrated in different models, the clinical response seems to be quite similar.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, only a few small clinical studies have directly compared ALA‐ with MAL‐PDT and this has only been done for AKs and nBCC. To our knowledge, no studies have compared the efficacy of ALA‐ and MAL‐PDT for sBCC and BD . Although in vitro studies have shown some differences concerning penetration and accumulation between the two compounds, which can be demonstrated in different models, the clinical response seems to be quite similar.…”
Section: Discussionmentioning
confidence: 98%
“…Another comparative retrospective study on facial AKs showed similar efficacy, recurrence rates, cosmetic outcomes and adverse events between MAL‐PDT ( n = 29) and ALA‐PDT ( n = 29) after 12 months with an application time of 3 h for MAL and 6 h for ALA. However, MAL‐PDT was significantly less painful than ALA‐PDT . Recently, however, the nanoemulsion BF‐200 ALA was compared with MAL for thin/moderate thickness AKs in the face and scalp with higher complete clearance rates with BF‐200 ALA‐PDT (78%) as compared to MAL‐PDT (64%) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the reason why AK should be treated is because we cannot predict which AK will transform into an invasive SCC. Various therapeutic approaches have been used for the treatment of AKs, including lesion-specific therapies, such as cryotherapy, laser therapy, and curettage, as well as field-directed therapies, such as imiquimod and topical photodynamic therapy 1416. While deciding on the treatment method, a number of factors should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…6-8 The reasons are related with the concentration of photosensitizer, energy of light, skin conditions of patients, and so on. But we cannot ignore that the whole face irradiation lack of accuracy is also an important reason.…”
Section: Introductionmentioning
confidence: 99%